Message accession - Mackehenie, Daniel (1952)
I have agreed to stubborn requirement to evoke student atmosphere in the last years of the last century and the impression that we caused the Spanish discoveries distinguished scholar; For if I still have - very amenguadamente as you can imagine - the memory of what happened when I started medical studies, which were for past always better times, I fear not being able to communicate what experienced as distant time an audience, afflicted with premiosos duties that we face today.